ANALISIS KINERJA AGRIBISNIS PERBENIHAN KEDELAI (BERBASIS PROGRAM) DI KECAMATAN PANCATENGAH KABUPATEN TASIKMALAYA - Abid Ubaidillah; Trisna Insan Noor; Meddy Rachmadi (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
The use of quality seeds in Indonesia for new soybean commodities is around 3%, the problem of quality seeds for farmers is not available when needed. Government policies to encourage the use of quality seeds at the farm level are through direct assistance of superior seeds (BLBU), and the establishment of seed independent villages. Then carried out improvements in cultivation techniques and in the institutional setting to form a seed supply system that is agribusiness and sustainable. Therefore, this study aims to analyze the agribusiness aspects of sustainable soybean seedling in Tasikmalaya Regency viewed from the five dimensions of sustainability namely the economic dimension, social dimension, environmental dimension, technological dimension, and institutional dimension. The analysis used is quantitative descriptive with 192 respondents consisting of independent seed farmers, using cluster random sampling technique. The results of the study showed that the performance of sustainable soybean seed-based agribusiness programs performed well enough, which meant that improvements were still needed in each dimension so as to obtain maximum performance.